(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of this study is to determine the age of diagnosis of hearing impairment in children and outcome of early management in linguistic acquisition in hearing impaired children. Study Design: A descriptive cross-sectional study in cross section population. Place and Duration of Study: This study was conducted at the Otorhinolaryngology department of Abbasi Shaheed Hospital. This study was conducted from January 2022 to June 2023. Methods: Detail history and complete examination was done. Relevant investigations were performed. After fulfill the selection criteria, patients advised hearing amplification device and speech therapy. Patients called for follow-up and observe language development. Results: Total number of patients selected for this study was 105 patients. Female were 57 (54%). Female male ratio was 1.18. 38 (36%) children were between the ages of 2-3 years came first time in ENT department with complaining of hearing impairment followed by 1-2 years 33 (31%). 59 (56%) patients showed improvement in speech and language development while 46 (43.8%) patients showed poor performance in development of speech and language. Highest frequency of improvement in language development was observed between ages of 0-1 years 15 (78.9%) patients out of 19 patients. Poor performance in development of speech and language was noted between 3-4 years 2 (13.3%) out of 15 patients. Conclusion: Early diagnosis of hearing impairment and appropriate treatment observed good result in language development